2010
DOI: 10.1121/1.3277200
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound characterization of red blood cell aggregation with intervening attenuating tissue-mimicking phantoms

Abstract: The analysis of the ultrasonic frequency-dependent backscatter coefficient of aggregating red blood cells reveals information about blood structural properties. The difficulty in applying this technique in vivo is due to the frequency-dependent attenuation caused by intervening tissue layers that distorts the spectral content of signals backscattered by blood. An optimization method is proposed to simultaneously estimate tissue attenuation and blood structure properties, and was termed the structure factor siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 32 publications
(50 reference statements)
4
62
0
Order By: Relevance
“…The accurate prediction of the non-Newtonian behavior from simulations of cell suspensions suggests a new paradigm for rheology of cell suspensions and blood in particular. As an example, an abnormal increase in RBC aggregation is a pathological state associated with many diseases, such as deep venous thrombosis, atherosclerosis, AIDS, myeloma, and diabetes mellitus, which may afflict many different sites of the human arterial tree (37)(38)(39)(40). However, such correlations have had few theoretical guidelines for their interpretation.…”
Section: Ms-rbc (No Aggregation) Ms-rbc (Aggregation) Ld-rbc (No Aggrmentioning
confidence: 99%
See 1 more Smart Citation
“…The accurate prediction of the non-Newtonian behavior from simulations of cell suspensions suggests a new paradigm for rheology of cell suspensions and blood in particular. As an example, an abnormal increase in RBC aggregation is a pathological state associated with many diseases, such as deep venous thrombosis, atherosclerosis, AIDS, myeloma, and diabetes mellitus, which may afflict many different sites of the human arterial tree (37)(38)(39)(40). However, such correlations have had few theoretical guidelines for their interpretation.…”
Section: Ms-rbc (No Aggregation) Ms-rbc (Aggregation) Ld-rbc (No Aggrmentioning
confidence: 99%
“…However, such correlations have had few theoretical guidelines for their interpretation. The modeling of cells whose parameters are determined from experiments on single cells (41) can be extended to abnormal and diseased cells, and in combination with the aggregation model, their suspensions can be simulated to allow quantitative comparison with rheological measurements and to guide in vivo ultrasonic measurements to yield a more precise diagnosis of the aforementioned diseases (40). The predictive capability of accurate modeling of cell and capsule suspensions can be readily extended to a variety of engineering and material science applications.…”
Section: Ms-rbc (No Aggregation) Ms-rbc (Aggregation) Ld-rbc (No Aggrmentioning
confidence: 99%
“…To our knowledge, neither the PM nor the SFM have been tested so far in blood characterization studies as means of predicting the scatterer concentration because the hematocrit is assumed to be known a priori. 26 However, our study showed that the estimation of the scatterer concentration is not straightforward using the PM or the SFM. The following discussion intends to explain why the concentration estimates cannot be obtained directly using standard minimization procedures in the 6-22 MHz frequency bandwidth studied here.…”
Section: Inverse Problemmentioning
confidence: 69%
“…(7) in Ref. 26). In the present study, the reference scattering medium used was a suspension of polyamide microspheres with a radius of 2.5 µm (orgasol 2001 UD NAT1, Arkema, France) present at a low concentration of 0.5% and gently stirred in water.…”
mentioning
confidence: 96%
See 1 more Smart Citation